2018
DOI: 10.2188/jea.je20170006
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Great East Japan Earthquake on Body Mass Index, Weight, and Height of Infants and Toddlers: An Infant Survey

Abstract: BackgroundThe body mass index (BMI) of preschool children from 4 years of age through primary school has increased since the Great East Japan Earthquake, but that of children aged under 3 years has not been studied. This study evaluated how the anthropometrics of younger children changed following the earthquake.MethodsHeight and weight data of children living in northeast Japan were collected from 3-, 6-, 18-, and 42-month child health examinations. We compared the changes in BMI, weight, and height among inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Similarly, after the Great East Japan Earthquake, one of the cities in Rikuzentaka was most devastated by obesity prevalence, but BMI increased in children in temporary housing compared with permanent housing (Moriyama et al, 2018). On the contrary, Yokomichi et al (2018) found that Fukushima-affected babies and toddlers showed signs of development disruption and early adiposity rebound which can lead to obesity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similarly, after the Great East Japan Earthquake, one of the cities in Rikuzentaka was most devastated by obesity prevalence, but BMI increased in children in temporary housing compared with permanent housing (Moriyama et al, 2018). On the contrary, Yokomichi et al (2018) found that Fukushima-affected babies and toddlers showed signs of development disruption and early adiposity rebound which can lead to obesity.…”
Section: Discussionmentioning
confidence: 99%
“…These studies conclude that the exposed children normally had higher BMI and obesity prevalence as compared to the children not exposed to the disaster. Only a few studies focus on physical growth in early childhood (0-3 years) with similar conclusions (Ono et al, 2018;Yokomichi et al, 2018). Although most of these studies utilize longitudinal data, they compare the growth outcomes between the affected and unaffected children before and after the disaster without using robust statistical/econometric methods for causal analysis.…”
Section: Review Of Literaturementioning
confidence: 99%
“…The major categories of this impact are (1) obesity, (2) sedentary behaviour, and (3) psychological distress. Among children and adolescents after the Great East Japan Earthquake, there are the previous studies by Kawasaki et al ( 2020 ), Ohira et al ( 2019 ), Kuniyoshi et al ( 2019 ), Takahashi and Tsubokura ( 2018 ), Yokomichi et al ( 2018 ), Moriyama et al ( 2018 ), Isojima et al ( 2017 ), Kikuya et al ( 2017 ), Zheng et al ( 2017 ), Yokomichi et al ( 2016 ), Kawasaki et al ( 2015 ) and Kawasaki et al ( 2014 ) on obesity. And there are previous studies on the sedentary behavior by Goodwin et al ( 2020 ), Itagaki et al ( 2017 ) and Okazaki et al ( 2015 ).…”
Section: Similarities Between the Covid-19 Pandemic Conditions And Th...mentioning
confidence: 98%
“…In the Sendai Framework for Disaster Risk Reduction, it is stated that “Children and youth are agents of change and should be given the space and modalities to contribute to disaster risk reduction, in accordance with legislation, national practice and educational curricula” (4) . Although scientific evidence is accumulating around the consequences of the Fukushima nuclear accident on children’s physical and mental health (5) , (6) and more recently on their social life including bullying (7) , not much has been reported about the roles that children are taking in the disaster restoration.…”
Section: Introductionmentioning
confidence: 99%